THE EFFECTIVENESS OF HANDOUT LEARNING MEDIA BASED ON INQUIRY METHODS ON HEAT MATERIALS AND TRANSFER AT SD NEGERI 22 PALU - Yulandariani Yulandariani; Ni Made Mega Hariani; I Wayan Budi Agus Putrayasa (JATMIKA : Journal Education and Learning of Elementary School, 2023)
This study aims to determine the effectiveness and response of students to use handout learning media based on the inquiry method on heat material and its transfer at SD Negeri 22 Palu. The research design used is a pre-experimental design using a one group pre test post test model. The average student learning outcomes before using the handout media was 61.8 while the average student learning outcome after using the handout media was 80.6. The average difference in student learning outcomes is 19.5. Analysis of 8,209 and 1,703. Based on the analysis, it is stated that > so the handout learning media based on the inquiry method on heat and its transfer material is declared effective for use in class VB SD Negeri 22 Palu. The use of media handouts in learning received a positive response from students, Media handouts can arouse students' enthusiasm and curiosity about teaching materials.